The Virtual Public Thing: de-re-territorialisations of public space through shopping in Auckland’s urban space - Manfredo Manfredini; Ross Jenner (Interstices, 2015)
New recombinant factors emerging in urban public space counteract the increasing disjunction of urban places subject to commodification and privatisation. In low-density cities within neoliberal political frameworks, these factors have developed peculiar places of social relationship: the integrated urban enclosures devoted to lifestyle consumption that are the latest evolution of shopping centres. These enclosures are heterotopic places mobilised by spectacle that quickly subsume the fundamental changes occurring in the relations between architecture and associative life in our contemporary post-consumerist, digital era. The paper discusses a comparative analysis of the new mall typology recently introduced into Auckland, exploring the important challenge they pose to architecture and urban design in defining the future of public space.